SOA in action experiences with caching, transactions and security in a highly distributed, networked SOA in the travel and leisure industry. - Rafat, Armughan
LibGo Travel, one of the largest privately held travel companies in the U.S., provides vacation packages through its retail stores and wholesale distribution channels to consumers, partners, travel agents and stores. The company wanted to expand its offerings by adding dynamic, branded and personalized packages. To help execute this idea, LibGo had to bring together our travel partners, including airlines, hotels and travel aggregators, as well as LibGo Travel's existing heterogeneous systems environment. As a result, LibGo's Next Generation Travel System (NGTS) is among the most sophisticated booking systems that are currently being implemented. Instead of building one-off interfaces for each partner- a time consuming, expensive and brittle solution- LibGo adopted a moden SOA with shared business services and Web services : data interchange would be XML-based and WSDL would be the single interface definition standard.